2021
DOI: 10.3389/fphar.2020.607287
|View full text |Cite
|
Sign up to set email alerts
|

Netosis and Inflammasomes in Large Vessel Occlusion Thrombi

Abstract: The inflammatory response appears to play a critical role in clotting in which neutrophil extracellular traps (NETs) are the major drivers of thrombosis in acute ischemic stroke (AIS). The inflammasome is an innate immune complex involved in the activation of interleukin (IL)-18 and IL-1β through caspase-1, but whether the inflammasome plays a role in NETosis in AIS remains poorly understood. Here we assessed the levels of inflammasome signaling proteins in NETs and their association with clinical and procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 63 publications
4
28
0
Order By: Relevance
“…Indeed, we showed that speck formation occurs transiently in murine neutrophils before nuclear decondensation. Our results are reinforced by recent studies suggesting a link between NETs and the presence of extracellular inflammasomes 42,43 . Chen et al showed via electron microscopy and immunofluorescence that inflammasome signaling proteins like caspase-1 and ASC speck are present in NETs of human thrombi and associated with H3cit, the marker of NETosis 43 .…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, we showed that speck formation occurs transiently in murine neutrophils before nuclear decondensation. Our results are reinforced by recent studies suggesting a link between NETs and the presence of extracellular inflammasomes 42,43 . Chen et al showed via electron microscopy and immunofluorescence that inflammasome signaling proteins like caspase-1 and ASC speck are present in NETs of human thrombi and associated with H3cit, the marker of NETosis 43 .…”
Section: Discussionsupporting
confidence: 88%
“…66,93 Neutrophil extracellular traps (NETs) have been identified as part of the clot scaffold by using antibodies against NETosis biomarkers (citrullinated histones) and histochemical staining of extracellular DNA. 63,65,66,76,[93][94][95]99 NETs were visualized in almost all (79.1% to 100%) of the analyzed thrombi in different studies, 63,65,66,76,93,95 in amounts ranging Values are presented as weighted mean±pooled standard deviation or number. PLT, platelet; FBR, fibrin; RBC, red blood cell; WBC, white blood cell.…”
Section: Thrombus Structure and Composition: Advanced Imaging And Histopathologymentioning
confidence: 99%
“…76 NET signals were observed as being confined within cells, filopodia-like structures, or web-like structures, 65 especially in the outer thrombus layers, 63,95 and almost exclusively within FBR-rich areas. 76 Inside the NETs, citrullinated histones were co-localized with inflammasome proteins (caspase-1 and apoptosis-associated speck-like protein containing a caspase-recruitment domain [ASC]), 99 granular neutrophil proteins (MPO) and extracellular DNA released from neutrophils. 93,95 The addition of histone-DNA complexes to FBR resulted in thicker fibers accompanied by increased rigidity, which contributed to the structural complexity and stabilization of the thrombi.…”
Section: Thrombus Structure and Composition: Advanced Imaging And Histopathologymentioning
confidence: 99%
See 2 more Smart Citations